Association between neutrophil-lymphocyte ratio and all-cause and cardiovascular mortality in patients with diabetes or prediabetes with comorbid obstructive sleep apnea symptoms: evidence from NHANES 2005-2008 and 2015-2018 - He, Jin-Mao; Yang, Yi (Frontiers in Endocrinology, 2025)
ObjectiveThe neutrophil-lymphocyte ratio (NLR) is a hematological marker to assess systemic inflammation and immune status. The relationship between NLR and the risk of mortality in individuals with diabetes mellitus or pre-diabetes mellitus who have comorbid symptoms of obstructive sleep apnea is unknown. Our study aims to evaluate the association between NLR and all-cause and cardiovascular mortality in this population.MethodsOur research enrolled 5432 patients from the National Health and Nutrition Examination Surveys (2005-2008 and 2015-2018) diagnosed with diabetes or prediabetes combined with symptoms of OSA. Mortality outcomes were ascertained by linkage to the National Death Index (NDI) records for December 31, 2019. The association between NLR and mortality was tested using multivariate Cox regression models. The non-linear relationship was analyzed based on restricted cubic spline curves (RCS). Kaplan-Meier (K-M) survival analysis and time-dependent subject operating characteristic curve (ROC) analysis were performed to assess the predictive value of NLR on patient survival.ResultsIn a median follow-up period of 52 months, study participants experienced 632 deaths from all causes and 143 deaths due to cardiovascular disease. According to Cox regression analysis, the fourth quartile was associated with higher all-cause mortality (HR=1.76, 95% CI 1.25-2.49) and cardiovascular mortality (HR=3.08, 95% CI 1.54-6.18) compared with the first quartile under the fully adjusted model. Meanwhile, K-M survival curves showed that all-cause and cardiovascular mortality increased with increasing NLR levels, with the highest mortality in the fourth quartile group. In addition, the areas under the curve (AUC) of the 3, 5and 10year survival were 0.67, 0.63, and 0.74 for all-cause mortality, respectively. Meanwhile, the AUC values ​​for cardiovascular mortality were 0.73, 0.56, and 0.69.ConclusionFor individuals with diabetes and OSA symptoms, elevated NLR can serve as a prognostic indicator for all-cause and cardiovascular mortality.